The Impact Of Promotion On Instagram Social Media With The Aisas Model Approach In The Covid-19 Pandemic (Case Study On Ms.Glow Online Consumers) - Miraza, Zuwina; Titania, Febby Elda (Cattleya Darmaya Fortuna, 2024)
This research is a quantitative associative research. The population in this study were MS.Glow users on Instagram social media. Primary data obtained by questionnaire (Google Form). The data were analyzed using the Structural Equation Model – Partial Least Square (PLS) analysis technique. The results showed that promotion had a significant effect on Attention, Promotion had a significant effect on Interest, Promotion had a significant effect on Search, Attention had a significant effect on Action, Interest had no significant effect on Action, Search had a significant effect on Action, Promotion had a significant effect on Action through Attention, Promotion has no significant effect on Action through Interest, Promotion has no significant effect on Search through Attention, Action has a significant effect on Share, Attention has a significant effect on Share through Action, Interest has no significant effect on Share through Action, Search has a significant effect on Share through Action. Based on these results, it is concluded that promotion on social media can be seen its effect with the AISAS method and can increase sales effectively.